Sosialisasi Tata Kelola Koperasi Syariah untuk Meningkatkan Profesionalisme dan Akuntabilitas - Nur'aeni, Nur'aeni; Mintarsih, Mimin; Nugraha, Galih (Ma'soem University, 2025)
Bumiwangi Village is one of the villages located in the Ciparay District, Bandung Regency, which has considerable potential in tourism and community economy. However, on the other hand, this village still faces several challenges, particularly in the management of the Village Cooperative, namely the lack of understanding among cooperative administrators and members regarding the concepts, principles, and governance systems of a Sharia cooperative. This community service activity uses the ABCD (Asset Based Community Development) method, through several stages including the initial observation stage, the socialization implementation stage, the evaluation stage, and the follow-up and program sustainability stage. As a result of this activity, participants gain insight into the importance of transparency, accountability, responsibility, and professionalism in running cooperative activities.